Role of brand awareness, brand loyalty and customer citizenship behaviour in aviation sector of Pakistan - Raza, Mohsin; Md. Salleh, Salniza; Shaari, Hasnizam (2019)
Despite extensive research on customer citizenship behaviour, the influence of branding strategies remains a neglected area in field of marketing. This study investigates the relationship of branding strategies and customer citizenship behaviour. The proposed model is supported by stimulus organism response model. In addition, this study explains the mediating role of brand loyalty and effect of brand awareness on customer citizenship behaviour with mediating effect of brand loyalty. It is investigated that brand awareness generates brand loyalty of customers and this loyal behaviour of customers turns into citizenship behaviour which provide great assistance to brand and other customers. The findings of studies incorporate the ongoing problems of Pakistan aviation sector. Based on literature, theoretical and managerial implications are provided in this study